Сatatonia in Autism Spectrum Disorders: Diagnosis, Therapy and Clinical Science - Dhossche, D.M. (Autizm i narušenie razvitiâ, 2019)
Catatonia has been increasingly recognized as a comorbid syndrome of autism at a rate of 12—17% in adolescents and young adults with autism spectrum disorders. Symptoms that should alert the clinician for catatonia are markedly increased psychomotor slowness which may alternate with excessive motor activity, apparently purposeless, and not influenced by external stimuli, extreme negativism or muteness, stereotypy, peculiarities of voluntary movement, increased stereotypies with or without self-injury, echolalia, or echopraxia. Upsetting life events, the loss of routine and structure, experiences of loss, conflicts with parents, caregivers, or peers, and discrepancies between the ability in the patient and parental expectations-especially, in higher functioning autistic youth, are known to precipitate catatonia as well as medical and neurological illnesses. Lacking controlled trials, successful use of benzodiazepines, sometimes at high dosages, and electroconvulsive therapy for catatonia in autism is supported by case-reports and case-series. Electroconvulsive therapy is indicated for the treatment of catatonia when lorazepam does not bring about rapid relief. Maintenance electroconvulsive therapy is important for sustained symptom remission in some cases. There is an urgent need for prospective studies of catatonia in autism spectrum disorders and for controlled treatment trials. Кататония все чаще признается коморбидным по отношению к аутизму синдромом с уровнем распространенности 12—17% среди подростков и молодых людей с расстройствами аутистического спектра. Симптомы, которые должны настораживать клинициста на предмет возможной кататонии, — это психомоторная заторможенность, которая может чередоваться с чрезмерной двигательной активностью,очевидно бесцельной и не зависящей от внешних стимулов, крайним негативизмом, мутизмом, стереотипиями с самоповреждениями или без самоповреждений и причудливые движения, эхолалии или эхопраксии. Известно, что стрессовые события в жизни, нарушение привычного распорядка, переживание утраты, конфликты с родителями, опекунами или сверстниками и несоответствие способностей пациента и родительских ожиданий — особенно у молодежи с высокофункциональным аутизмом, а также соматические и неврологические заболевания, предшествуют кататонии. Немногочисленные контролируемые исследования, успешное использование бензодиазепинов, иногда в больших дозах, и электрошоковой терапии подтверждаются описаниями клинических случаев и их серий. Если лоразепам не дает быстрого облегчения, показана электрошоковая терапия. В некоторых случаях для поддержания стойкой ремиссии необходима поддерживающая электрошоковая терапия. Существует острая необходимость в проведении проспективных исследований кататонии при расстройствах аутистического спектра и в контролируемых исследованиях лечения. Перевод с английского Л.Г. Бородиной